Nordic diet and its benefits in neurological function: a systematic review of observational and intervention studies - Jafari, Reyhaneh Sadat; Behrouz, Vahideh (Frontiers in Nutrition, 2023)
Introduction Neurological disorders have been considered the major contributors to global long-term disability and lower quality of life. Lifestyle factors, such as dietary patterns, are increasingly recognized as important determinants of neurological function. Some dietary behaviors, such as Nordic diet (ND) were likely to have protective effects on brain function. However, an understanding of the effectiveness of the ND pattern to improve neurological function and brain health is not fully understood. We review the current evidence that supports the ND pattern in various aspects of neurological function and addresses both proven and less established mechanisms of action based on its food ingredients and biochemical compounds. Methods In this systematic review, PubMed, Web of Science, and Scopus databases were searched from inception to February 2023. Observational and intervention studies were included. Results Of the 627 screened studies, 5 observational studies (including three cohorts and two cross-sectional studies) and 3 intervention studies investigating the association between ND and neurological function. Observational studies investigated the association of ND with the following neurological functions: cognition, stroke, and neuropsychological function. Intervention studies investigated the effects of ND on cognition and depression. Discussion Despite the limited literature on ND and its association with neurological function, several aspects of ND may lead to some health benefits suggesting neuroprotective effects. The current state of knowledge attributes the possible effects of characteristic components of the ND to its antioxidant, anti-inflammatory, lipid-lowering, gut-brain-axis modulating, and ligand activities in cell signaling pathways. Based on existing evidence, the ND may be considered a recommended dietary approach for the improvement of neurological function and brain health. Systematic review registration [https://www.crd.york.ac.uk/prospero/], identifier [CRD2023451117].